THE CONCEPT OF JUSTICE IN THE MANAGEMENT AND UTILIZATION OF NATURAL RESOURCES BASED ON THE 1960 BASIC AGRARIAN LAW - M. Yazid Fathoni (Jurnal IUS Kajian Hukum dan Keadilan, 2013)
The Agrarian Law of 1960 is  basic rule for managing and exploiting natural resources  in Indonesian which one it’s aim is to create justice to both state and  citizen. Even though justice has been  established as it’s aim, but still the justice as stipulated in Agrarian Law of 1960 is unclear such as it’s definition, standing and position, function, as well as it’s profile and character. Such vagueness impacts on variety of things including the final purpose to which the law directs. Nevertheless, theoretically, the justice on the perspective of Agrarian Law of 1960 is relatively closer to utilitarianism theory has i.e. to create the happiness and welfare for the greatest number of Indonesian people. Finally, according to utilitarianism perspective, the happiness and welfare supposes to be enjoyed and possessed  by every body, or if it can’t be realized,  at least by the greatest number of people.  Keywords: Natural Resources, Managing,  Justice